Atmospheric Electricity Influencing Biogeochemical Processes in Soils and Sediments - Hunting, Ellard R.; Harrison, R. Giles; Bruder, Andreas; van Bodegom, Peter M.; van der Geest, Harm G.; Kampfraath, Andries A.; Vorenhout, Michel; Admiraal, Wim; Cusell, Casper; Gessner, Mark O. (Frontiers in Physiology, 2019)
The Earth’s subsurface represents a complex electrochemical environment that contains many electro-active chemical compounds that are relevant for a wide array of biologically driven ecosystem processes. Concentrations of many of these electro-active compounds within Earth’s subsurface environments fluctuate during the day and over seasons. This has been observed for surface waters, sediments and continental soils. This variability can affect particularly small, relatively immobile organisms living in these environments. While various drivers have been identified, a comprehensive understanding of the causes and consequences of spatio-temporal variability in subsurface electrochemistry is still lacking. Here we propose that variations in atmospheric electricity (AE) can influence the electrochemical environments of soils, water bodies and their sediments, with implications that are likely relevant for a wide range of organisms and ecosystem processes. We tested this hypothesis in field and laboratory case studies. Based on measurements of subsurface redox conditions in soils and sediment, we found evidence for both local and global variation in AE with corresponding patterns in subsurface redox conditions. In the laboratory, bacterial respiratory responses, electron transport activity and H2S production were observed to be causally linked to changes in atmospheric cation concentrations. We argue that such patterns are part of an overlooked phenomenon. This recognition widens our conceptual understanding of chemical and biological processes in the Earth’s subsurface and their interactions with the atmosphere and the physical environment.